Readiness and DADT Repeal: Has the New Policy of Open Service Undermined the Military?. (October 2013) - Belkin, Aaron; Ender, Morten G.; Frank, Nathaniel; Furia, Stacie R.; Lucas, George; Packard, Gary; Samuels, Steven M.; Schultz, Tammy; Segal, David R.
Prior to the repeal of "don't ask, don't tell" (DADT) on September 20, 2011, many observers predicted that allowing lesbian, gay and bisexual troops to serve openly would harm the military, and a group of more than 1, 000 retired general and flag officers predicted that repeal could "break the All-Volunteer Force." This study is the first scholarly effort to assess the accuracy of such predictions about the impact of DADT repeal on military readiness. We conducted our research during the half-year period starting six months after repeal and concluding at the one year mark, and we pursued ten separate research strategies including in-depth interviews, survey analysis, on-site field observations, pretest/posttest quasi experimentation, secondary source analysis, and a comprehensive review of media articles. Our goal was to maximize the likelihood of identifying evidence of damage caused by repeal, and we made vigorous efforts to collect data from repeal opponents including anti-repeal generals and admirals, activists, academic experts, service members and watchdog organizations. Our conclusion, based on all of the evidence available to us, is that DADT repeal has had no overall negative impact on military readiness or its component dimensions, including cohesion, recruitment, retention, assaults, harassment, or morale. If anything, DADT repeal appears to have enhanced the military's ability to pursue its mission.